Molecular-genetic bases of plumage coloring in chicken - A. V. Makarova; O. V. Mitrofanova; A. B. Vakhrameev; N. V. Dementeva (Вавиловский журнал генетики и селекции, 2019)
The color of plumage in birds is an important feature, often determining descent to a particular species or breed. It serves as a key factor in the interaction of birds with each other due to their well-developed visual perception of the surrounding world. In poultry including chickens, the color of the plumage can be treated as a genetic marker, useful for identifying breeds, populations and breeding groups with their specific traits. The origin of diverse color plumage is the result of two interrelated physical processes, chemical and optical, due to which pigment and structural colors in the color are formed. The pigment melanin, which is presented in two forms, eumelanin and pheomelanin, is widely spread in birds. The basis for the formation of melanin is the aromatic amino acid tyrosine. The process of melano-genesis involves many loci, part of the complex expression of plumage color genes. In birds, the solid black color locus encodes the melanocortin 1 receptor (MC1R), mutations in which lead to a change in receptor activation and form different variants of the E locus. Using the GWAS analysis, possible genes affecting the formation of color in chickens were detected. The biosynthesis and types of melanin are affected by the activity of the enzyme tyrosine, and mutations in the tyrosinase gene (TYR) cause albinism in different species. The formation mechanism of brown, silver, gold, lavender and a number of other shades is determined by the influence on the work of the MC1R genes and TYR specific modifier genes. Thus, locus I currently associated with the PMEL17 gene inhibits the expression of eumelanin, and the MLPH gene affects tyrosinase function. Research on the mechanisms of formation of the secondary coloring of plumage in chickens is being actively conducted nowadays. The formation of a marble feather pattern is associated with the mutation of the endothelin B2 receptor (EDNRB2), in the coding part of the gene of which a polymorphism is found associated with the mo locus. The molecular base that causes the feather banding (locus B and autosomal recessive banding) is identified. Today, only some genes that determine the color of the plumage of chickens are studied and described. Different genes can produce similar plumage patterns, and different phenotypes can be determined by the polymorphism of a single gene. Using molecular methods, you can more accurately identify these differences. This overview shows the nature of melanin coloration in birds using the example of chickens of various breeds and also attempts to systematize knowledge about the molecular-genetic mechanisms of the appearance of various types of coloration.